2002
DOI: 10.1128/jvi.76.6.2634-2640.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Kaposi's Sarcoma-Associated Herpesvirus (KSHV)-Specific Cytotoxic T-Lymphocyte Epitopes and Evaluation of Reconstitution of KSHV-Specific Responses in Human Immunodeficiency Virus Type 1-Infected Patients Receiving Highly Active Antiretroviral Therapy

Abstract: Following the introduction of highly active antiretroviral therapy (HAART), the incidence of Kaposi's sarcoma (KS) has significantly declined in human immunodeficiency virus type 1 (HIV-1)-positive (HIV-1 ؉ ) individuals and clinical remission is often observed. We hypothesize that these effects are partly due to anti-KS-associated herpesvirus (KSHV) immune restoration. Here, 15-mer overlapping peptides from proteins K12 and K8.1 were used to identify novel KSHV-specific cytotoxic T-lymphocyte epitopes. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
66
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 30 publications
5
66
0
2
Order By: Relevance
“…While cellular responses to KSHV infection have been studied, our understanding of antibody response to KSHV or in the context of KSHV infection is very limited. The general consensus is that KSHV-specific responses are frequent, diverse, and strongly differentiated toward an effector phenotype (CTLs) in patients who control the infection (42)(43)(44)(45)(46). Conversely, KSHV-specific CTLs are very rare in patients who progress to KS, supporting the crucial role of cellular immune responses in controlling KSHV replication, preventing malignancies and conferring resistance to persistent infection (42)(43)(44)46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While cellular responses to KSHV infection have been studied, our understanding of antibody response to KSHV or in the context of KSHV infection is very limited. The general consensus is that KSHV-specific responses are frequent, diverse, and strongly differentiated toward an effector phenotype (CTLs) in patients who control the infection (42)(43)(44)(45)(46). Conversely, KSHV-specific CTLs are very rare in patients who progress to KS, supporting the crucial role of cellular immune responses in controlling KSHV replication, preventing malignancies and conferring resistance to persistent infection (42)(43)(44)46).…”
Section: Discussionmentioning
confidence: 99%
“…The general consensus is that KSHV-specific responses are frequent, diverse, and strongly differentiated toward an effector phenotype (CTLs) in patients who control the infection (42)(43)(44)(45)(46). Conversely, KSHV-specific CTLs are very rare in patients who progress to KS, supporting the crucial role of cellular immune responses in controlling KSHV replication, preventing malignancies and conferring resistance to persistent infection (42)(43)(44)46). Although in few cases of MCD polyfunctional KSHV-specific CD8 responses have been observed, suggesting that cellular immunity is less protective in MCD than in KS, a level of immune escape is present also in MCD but restricted to fully differentiated effector memory CD8 + T cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of CTL responses against both latent and lytic HHV-8 proteins has recently been characterized (8 -11) but, thus far, only a few immunogenic CTL epitopes have been identified within these Ags (12)(13)(14)(15)(16). At present, the role the identified epitope-specific CTL responses play in control of HHV-8-infected cells or HHV-8-positive tumors is not known.…”
mentioning
confidence: 99%
“…H uman herpesvirus 8 (HHV-8), 3 also known as Kaposi's sarcoma-associated herpesvirus (KSHV) is the etiological agent of several infectious diseases including Kaposi's sarcoma, primary effusion lymphoma (PEL), and multicentric Castleman's disease (1). Like other herpesviruses, HHV-8 is able to establish a predominantly latent, life-long infection in its host.…”
mentioning
confidence: 99%
“…The increased incidence of these diseases in immunocompromised individuals suggests that host immune control may be essential in preventing HHV-8-associated diseases (2). Several studies have demonstrated the anti-HHV-8 specificity of TCR ␣␤ ϩ CD8 ϩ CTL (3)(4)(5)(6)(7)(8)(9)(10). HHV-8 specific CTL responses to latent and lytic viral proteins have been detected during primary HHV-8 infection (11).…”
mentioning
confidence: 99%